Phytochemical study and structural determination of the isolated product of Ricinus communis (Euphorbiaceae) - Andrianarijaona Mamy; Ralaivaon-dratsitonta Jumaël Edith Fabrice; Fatiany Pierre Ruphin; Robijaona Rahelivololoniaina Baholy (Britain International for Academic Research (BIAR) Publisher, 2025)
A phytochemical and structural study of the leaves of Ricinus communis (castor bean plant) was conducted to identify and characterize its active compounds. The plant material, sourced from Madagascar, was subjected to sequential maceration with solvents of increasing polarity, yielding hexane, dichloromethane (DCM), and methanolic extracts. Phytochemical screening revealed the presence of polysaccharides as the most abundant components, with moderate amounts of steroids and low concentrations of alkaloids and saponins. The DCM extract was further purified using thin-layer chromatography and column chromatography, leading to the isolation of a pure compound. Structural elucidation was performed using mass spectrometry (EI-MS) and one- and two-dimensional nuclear magnetic resonance (NMR) spectroscopy, including 1H, 13C, and DEPT-135 experiments. The spectroscopic data established a molecular formula of C28H46O and a tetracyclic steroid structure with two degrees of unsaturation. A comparison of the obtained chemical shifts with those reported in the literature confirmed the compound's identity as Brassicosterol, a key phytosterol.